The Effect of Practice-Based Fire Education on Community Knowledge in Kelutan Village, Ngronggot District, Nganjuk Regency - Sulistyorini Sulistyorini; Ima Nadatien; Imro'atul Alivia; Diaz Ramadhan Herlambang; Siti Nur Hasina (CV. Publikasi Indonesia, 2025)
Uncontrolled fires can cause significant environmental damage, material losses, and casualties, making community preparedness crucial. In Kelutan Village, Nganjuk Regency, many residents have limited knowledge about fire prevention and management, particularly regarding land fires, which are common due to strong winds and long dry seasons. This study aims to analyze the impact of practice-based fire education on increasing community knowledge. A pre-experimental design with a One Group Pre-test - Post-test approach was used, involving 95 community leaders and village officials from Kelutan Village selected through purposive sampling. The independent variable was practice-based fire education, and the dependent variable was community knowledge. A questionnaire with 20 pre-test and post-test items, tested for validity and reliability, was used as the research instrument. Data analysis was conducted using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The results showed that 72.6% of respondents had a moderate knowledge level before the intervention, which increased to 86.3% in the high category after receiving practice-based education. Statistical analysis revealed a p-value of 0.000 (p < α), indicating a significant effect of practice-based fire education on community knowledge. The study concludes that hands-on fire education is more effective than theoretical methods in improving public understanding, which is essential for enhancing fire prevention and management preparedness. Village authorities are encouraged to conduct regular and comprehensive fire education programs to better prepare the community.